Desenvolvimento de Materiais Termorresponsivos de Copolímeros de Poli(N-Isopropilacrilamida) com Goma do Cajueiro e seus derivados. - Sombra, Venícios Gonçalves (2019)
Thermoresponsive polymers have been proposed for drug loading and delivery systems, being the prominent systems those based on poly(N-isopropylacrylamide) (PNIPAAm) copolymers due to its thermoresponsive temperature close to human body temperature. Polysaccharides are applied to PNIPAAm copolymers formation providing new properties such as biodegradability and biocompatibility, besides allowing the transition temperature modulation. The present work studies copolymers formation of cashew gum (CG) and derivatives with amino terminated PNIPAAm (PNIPAAmNH2) by two routes: Schiff base and carbodiimide chemistry. PNIPAAmNH2 100 and PNIPAAmNH2 250 were synthesized, besides the GC oxidation (GCOX) and carboxymethylation (GCCM). GCOX and two differents PNIPAAmNH2 were used in mass ratios of 5:1 and 1:1 in Schiff base copolymerization reactions. Copolymerization reactions by carbodiimide used GCCM and GC with PNIPAAmNH2 250. GCOX copolymers produced thermoresponsive colloids with particle sizes, at 37 °C, ranging between 147.1 and 221.3 nm, and PdI from 0.151 to 0.580. Copolymers from PNIPAAmNH2 250 exhibit the lowest LCST (35 °C) that is uninfluenced by the mass ratio. The copolymers formed by Schiff base are stable in pH range from 4.0 to 7.4. Copolymers formed by the carbodiimide reaction presented LCST at 36 ° C, with particle sizes values of 194.3 and 262.4 nm, and PdI 0.109 and 0.345. It was observed that increasing the amount of PNIPAAmNH2 the systems becomes more homogeneous with lower PdI, especially systems: GCOX-g-PNIPAAmNH2 250 1:1, size 221.3 nm and PdI 0.151; GCOX-g-PNIPAAmNH2 250 1:1, size 194.3 nm and PdI 0.202; GC-g-PNIPAAmNH2 250 1:1, size 212.8 nm and PdI 0.109.